Networked Virtual Environments as a Communication Tool for Distance Learning - Fabri, Marc (Proceedings of the International Conference on Networked Learning, 1998)
This paper describes an ongoing PhD research project at Leeds Metropolitan University. It investigates the usability and potential benefits of Networked Virtual Environments as tools for communication and collaboration in Distance Learning systems. The project explores the interface aspects of a system conducting the virtual counterpart of face-to-face communication with regard to user representation, change of representation and perception of the interlocutor within a virtual world. As pan of the research, a prototype three-dimensional, multi-user environment will be created supporting computer-mediated verbal communication as well as non-verbal communication based on the use of visual metaphors in the virtual world. Furthermore, the research will consider opportunities for effective group work in a virtual study room, based on discussion and discourse.